Sustaining National Struggle Values for Child Well-Being: MBG Program and SDG 4 Achievement in Indonesian Elementary Schools - Dela Safitri; Sakinah Humaidi Al Khairiyah Nasution; Juttalee Petsong (Yayasan Zia Salsabila, 2026)
Prior studies on social disintegration in Indonesia have predominantly examined identity conflict and political polarization, with limited attention to preventive educational interventions at the elementary level, particularly regarding the Free Nutritious Meal (MBG) program and child well-being. Addressing this gap, this study explores how revitalization of national struggle values through contextual and participatory learning contributes to strengthening students' national spirit in Kendari City elementary schools while supporting Sustainable Development Goal 4 (SDG 4). A qualitative interpretive approach was employed, involving 18 informants from three public elementary schools through in-depth interviews, participatory observation, and document analysis. Data were analyzed using NVivo 14 via inductive thematic analysis. Three principal findings emerged: (1) inquiry-based learning effectively enhances civic literacy and national awareness; (2) integration of historical values with MBG program contexts strengthens children's socio-emotional well-being; and (3) teachers function as value facilitators transforming struggle narratives into tangible social actions. This study contributes to historically grounded character education theory and offers policy implications for elementary curriculum reform responsive to contemporary social disintegration threats in Indonesia.